PENGARUH ONLINE CUSTOMER RATING DAN ONLINE CUSTOMER REVIEW TERHADAP KEPUTUSAN PEMBELIAN PRODUK FASHION PADA PENGGUNA MARKETPLACE TIKTOK SHOP TANGERANG TAHUN 2024 - Majid, Amalia Sandya; Yasaningthias, Ghita (JAMBIS : Jurnal Administrasi Bisnis, 2024)
This study aims to analyze how much influence online customer ratings and online customer reviews have on purchasing decisions for fashion products at the TikTok Shop Tangerang marketplace. This study uses quantitative research methods with explanatory research types. The population in this study consisted of TikTok Shop marketplace users. The sample used was 120 respondents with Non-Probability Sampling sampling technique with Accidental Sampling approach. The data analysis methods used in this study are instrument test, classical assumption test, hypothesis testing and multiple linear regression test. The results showed that online customer rating has a positive and significant effect on purchasing decisions with a percentage of 84.6%. Online customer review has a positive and significant effect on purchasing decisions with a percentage of 88.2%. The amount of online customer rating and online customer review on purchasing decisions with a percentage of 89.6%.